IMPLEMENTASI KURIKULUM 2013 PADA PROSES PEMBELAJARAN EKONOMI DI SMA N 2 SUNGAI RAYA - Irawati, Irawati; Buwono, Sri; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out how the implementation of the 2013 curriculum in the process of economic learning in SMA N 2 Sungai Raya. This is seen from the learning planning, learning implementation and learning assessment. This study uses qualitative methods in a descriptive form. Data collection tools use observation guides, interviews, and documentation. The results of this study indicate 1) learning plans compiled by teachers in implementing the 2013 curriculum in the process of economic learning in SMA N 2 Sungai Raya are in accordance with the process standards set by the Ministry of Education and Culture 2) implementation of learning in implementing the 2013 curriculum in the economic learning process at SMA N 2 Sungai Raya already using a scientific approach in the core activities 3) learning assessment in implementing the 2013 curriculum in the economic learning process at SMA N 2 Sungai Raya has used process assessment and outcome assessment.Â Keywords: 2013 Learning , Economic Learning, Learning Process